The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/ndt.s128138
|View full text |Cite
|
Sign up to set email alerts
|

Delirium after a traumatic brain injury: predictors and symptom patterns

Abstract: BackgroundDelirium in traumatic brain injury (TBI) is common, may be predictable, and has a multifaceted symptom complex. This study aimed to examine: 1) the sum score of Glasgow Coma Scale (GCS) and if its component scores could predict delirium in TBI patients, and 2) the prominent symptoms and their courses over the first days after TBI.MethodsTBI patients were recruited from neurosurgical ward inpatients. All participants were hospitalized within 24 hours after their TBI. Apart from the sum score of GCS, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 19 publications
4
50
1
2
Order By: Relevance
“…Agitation and delirium can occur in up to 50% of patients with mild to moderate TBI in the first 4 days after the trauma. 25 Posttraumatic delirium is thought to be caused by neuro-inflammation, neurotransmitter imbalance, and structural brain damage. 26 Although the incidence of delirium is high in TBI patients, previous studies have not demonstrated that TBI is associated with a longer duration of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Agitation and delirium can occur in up to 50% of patients with mild to moderate TBI in the first 4 days after the trauma. 25 Posttraumatic delirium is thought to be caused by neuro-inflammation, neurotransmitter imbalance, and structural brain damage. 26 Although the incidence of delirium is high in TBI patients, previous studies have not demonstrated that TBI is associated with a longer duration of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] Another study investigated traumatic brain injury patients in the neurosurgical ward, concluded that those with low GCS score on admission in the emergency department were more likely to have delirium in the first 4 days after admission. [ 39 ]…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…13 It is estimated that posttraumatic delirium may affect up to half of patients with mild or moderate head injuries within the first 4 days following the trauma. 14 The association between posttraumatic delirium and suicide is not known; however, the results of a recent metaanalysis 5 indicate a moderate association between psychomotor agitation (which is a component of delirium) and the risk of suicide. However, further research will be necessary in order to examine the short-term risk of suicide in this patient population, given that posttraumatic delirium is not manifested in a homogeneous manner in the various clinical populations.…”
Section: Discussionmentioning
confidence: 99%